A benchmark shaking table test on the seismic responses of an extra‐large LNG storage tank. (5th November 2022) - Zhang, Ding‐Yuan; Wu, Jian‐Ying; Zhou, Hao; Gong, Mo‐Song
Abstract: In recent years, many large‐scale liquefied natural gas (LNG) storage tanks have been built all over the world. Due to their high constructional cost and important functions to the public, the academic and engineering communities are very concerned with the operational safety of these important infrastructures once subjected to potentially disastrous actions, that is, earthquakes, typhoons, tsunamis, and so forth. This work presented a benchmark test in evaluating the aseismic performance of extra‐large prestressed reinforced concrete (RC) LNG storage tanks. A 1:14 scaled model of the prototype LNG tank was designed and constructed for shaking table tests. Two recorded and two artificial earthquake ground motions with peak ground acceleration (PGA) up to 1.2 g were selected successively as seismic inputs to the tank. The acceleration, displacement, shear force, and strain responses of the model structure were presented, analyzed, and discussed in detail. It was found that due to the differences in the frequency spectra, the seismic excitations have distinct influences on the responses of the tank model. In particular, the wall‐roof junction was detected as the weakest part of the outer tank, and the filling water had non‐negligible effects on the overall seismic responses of the tank. Verified finite element simulations were also presented as supplements to the experimental study. Some suggestions were made with the aim to improve the designs of LNG storage tanks.